The health and well-being effects of drought: assessing multi-stakeholder perspectives through narratives from the UK - Kimberly Bryan; Sarah Ward; Liz Roberts; Mathew P. White; Owen Landeg; Tim Taylor; Lindsey McEwen (Climatic Change, 2020)
The global literature on drought and health highlights a variety of health effects for people in developing countries where certain prevailing social, economic and environmental conditions increase their vulnerability especially with climate change. Despite increased focus on climate change, relatively less is known about the health-drought impacts in the developed country context. In the UK, where climate change–related risk of water shortages has been identified as a key area for action, there is need for better understanding of drought-health linkages. This paper assesses people’s narratives of drought on health and well-being in the UK using a source-receptor-impact framing. Stakeholder narratives indicate that drought can present perceived health and well-being effects through reduced water quantity, water quality, compromised hygiene and sanitation, food security, and air quality. Heatwave associated with drought was also identified as a source of health effects through heat and wildfire, and drought-related vectors. Drought was viewed as potentially attributing both negative and positive effects for physical and mental health, with emphasis on mental health. Health impacts were often complex and cross-sectoral in nature indicating the need for a management approach across several sectors that targets drought and health in risk assessment and adaptation planning processes. Two recurring themes in the UK narratives were the health consequences of drought for ‘at-risk’ groups and the need to target them, and that drought in a changing climate presented potential health implications for at-risk groups.